Everyday pornography - Boyle, Karen, 1972- (London ; Routledge, 2010)
Drawing on the experiences of activists alongside academics,'Everyday Pornography' offers the opportunity to explore the intellectual & political challenges of anti-pornography feminism & consider its relevance for contemporary academic debate.
Arresting images : anti-pornography slideshows, activism and the academy / Gail Dines, Linda Thompson, Rebecca Whisnant, with Karen Boyle -- Methodological considerations in mapping pornography content / Ana Bridges --'Now that's pornography' : violence and domination in adult video news / Meagan Tyler -- Repetition and hyperbole : the gendered choreographies of heteroporn / Susanna -- Paasonen -- Cocktail parties : fetishizing semen in pornography beyond bukkake / Lisa Jean Moore & Juliana Weissbein -- Virtually commercial sex / Sarah Neely -- Pornography is what the end of the world looks like / Robert Jensen -- From jekyll to hyde : the grooming of male pornography consumers / Rebecca Whisnant -- Porn consumers' public faces : mainstream media, address and representation / Karen Boyle -- To catch a curious clicker : a social network analysis of the online pornography industry / Jennifer A. Johnson -- Young men using pornography / Michael Flood --'Students study hard porn' : pornography and the popular press / Mark Jones & Gerry Carlin -- Marginalising feminism : debating extreme pornography laws in public and policy discourse / Clare McGlynn.
Includes bibliographical references (p. [212]-235) and index.
Keywords: Pornography -- Social aspects; Sex in mass media; Pornography in popular culture